The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.jchemed.7b00439
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Chemistry Majors for the 21st Century through a Comprehensive One-Semester Course Focused on Professional Preparation, Contemporary Issues, Scientific Communication, and Research Skills

Abstract: Success in chemistry in the 21st century requires not only a mastery of important chemical concepts, but also the skills to apply this knowledge to important societal issues and the ability to effectively convey scientific information using a range of media. In response to this challenge we have developed an innovative four-credit seminar that comprehensively integrates the skills needed for chemistry majors to become successful professionals and experts in the chemistry field. It is expected that after taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In the chemistry context, they would acquire the knowledge needed in responsible research-based decision making and promoting sustainable development. 14 There has been little research on the societal dimension in chemistry education, but Marteel-Parrish and Lipchock 22 have suggested that understanding the societal role of chemistry is one of the key competencies for the 21 st century.…”
Section: Societal Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In the chemistry context, they would acquire the knowledge needed in responsible research-based decision making and promoting sustainable development. 14 There has been little research on the societal dimension in chemistry education, but Marteel-Parrish and Lipchock 22 have suggested that understanding the societal role of chemistry is one of the key competencies for the 21 st century.…”
Section: Societal Perspectivementioning
confidence: 99%
“…If students don't see the possible career opportunities, it decreases their will to choose chemistry. 23 The vocational perspective can be offered via individual career courses 24 or embedding career planning inside other courses 22 . Also, there is evidence that authentic research-based laboratory experiences support interest in chemistry careers 25 .…”
Section: Vocational Perspectivementioning
confidence: 99%
“…At the same time, learners' behaviors will affect the development direction of events, making learning like life and games. On the other hand, teachers can also play a role in the virtual environment and coordinate learning with learners to form a harmonious, interactive and cooperative teaching relationship (Marteel-Parrish and Lipchock, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, graduates in all disciplines must be able to confidently and competently use technologyin particular, to assist in processes such as data management and analysis [101]. Explaining computational ideas in the context of biology could be taught authentically utilising bioinformatics methodology as the context; bioinformatics is an important skill utilised by the modern biochemist, and it is recommended to be taught at the undergraduate level [102][103][104][105][106].…”
Section: Technology Skillsmentioning
confidence: 99%